Methods to modify supersaturation rate in membrane distillation crystallisation: control of nucleation and crystal growth kinetics (including scaling) - Ouda, Alaa Samir; Bajón Fernández, Yadira; McAdam, Ewan (Elsevier, 2024)
While water vapour flux is often regarded as the critical parameter in membrane distillation crystallisation (MDC), there are multiple factors that will determine the kinetics of nucleation and crystal growth. A Nývlt-like equation is therefore introduced that can relate how multiple conditional parameters (membrane area, flux, temperature difference, crystalliser volume, magma density) independently modify nucleation rate and supersaturation, enabling a normalising approach for the characterisation of nucleation and crystal growth kinetics within MDC. Each parameter can be modified to increase supersaturation rate, which reduced induction time and broadened the metastable zone width (MSZW) at induction. An increase in supersaturation mitigated scaling and favoured bulk nucleation. This is due to the increase in volume free energy provided by the elevated supersaturation that reduces the critical energy requirement for nucleation to favour a homogeneous primary nucleation mechanism. An increase in temperature difference or magma density narrowed the MSZW. For each parameter, either supersaturation rate, supersaturation or induction time were fixed, while the other two factors were amended. While higher supersaturation rates generally favoured larger crystal sizes with broader size distributions, a high level of supersaturation at a low supersaturation rate increased particle size and narrowed the size distribution. In practice, these factors may be applied collectively and synergistically to deliver strict control over crystal growth, which remains a challenge for current evaporative technology. This was illustrated when facilitating an increase in supersaturation rate with membrane area, where an identical nucleation order was identified between membrane systems, from which it can be implied that MDC affords an inherently scalable solution for crystallisation.
Keywords: Brine management; Resource recovery; Crystal growth; Hollow fibre; Zero-liquid discharge